KEGIATAN PENGABDIAN KEPADA MASYARAKAT (PkM) DONOR DARAH DI STIKES BETHESDA TOMOHON - Andro Ruben Runtu; Meilita Enggune; Djoise Kaunang; Elizabeth Purba; Welmin Lumi; Nolla Lisa Lolowang; Grace Merentek; Rivolta Musak; Angelia Pondaa; Ever Lontaan; Jeane Sumarauw; Marieska Waworuntu; Agustinus Langitan (COVIT (Community Service of Health), 2023)
This community service activity aims to provide additional blood stock to PMI that can be used by people who need blood. PkM blood donor participants totaling 41 donors which is an important part in efforts to balance blood demand and stock. It is hoped that the participants will benefit from this activity, if done sincerely, this endeavor is very noble and will be beneficial for the giver, so that the participants are very enthusiastic about participating in community service activities for blood donors at STIKES Bethesda Tomohon. Keywords: Community Service, Blood Donation